2021
DOI: 10.26905/jbm.v8i2.5797
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Komitmen Organisasi melalui Penguatan Efikasi Diri dan Kualitas Kehidupan Kerja

Abstract: Competition for universities in Indonesia, especially private universities, is always getting tougher every year. The number of existing private universities increasingly provides competitive value with the aim of working on prospective students so that the chosen institution or college remains superior and attractive and remains in demand. The purpose of this study was to examine the effect of self-efficacy and quality of work life on organizational commitment. This type of research is quantitative research u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
2
3
0
4
Order By: Relevance
“…Previous research stated a positive and significant relationship between self-efficacy and employee organizational commitment (Agustin et al, 2021). This statement is in line with an earlier study that found that self-efficacy and quality of work life affect organizational commitment with the subject of lecturers at a private university (Qurbani & Solihin, 2021).…”
Section: Introductionsupporting
confidence: 92%
“…Previous research stated a positive and significant relationship between self-efficacy and employee organizational commitment (Agustin et al, 2021). This statement is in line with an earlier study that found that self-efficacy and quality of work life affect organizational commitment with the subject of lecturers at a private university (Qurbani & Solihin, 2021).…”
Section: Introductionsupporting
confidence: 92%
“…All kinds of strong internal control over the work being done can form a person's belief to do a good job, then it can stimulate better and meaningful behavior as a more responsible and more committed attitude in the work he does. As what was found in the research of Qurbani & Solihin [16] which found a significant effect of self-efficacy on organizational commitment in work life. The study also found an increase in employee organizational commitment in their work life through efforts to strengthen self-efficacy.…”
Section: Self-efficacy On Employee Commitmentsupporting
confidence: 80%
“…Quality of work life dapat dikatakan sebagai teknik dalam mengembangkan perusahaan dimana sudah ada rancangan dalam pengembangan untuk peningkatan dalam fungsi yang dapat memanusiakan karyawan serta lingungan kerjanya sehingga dapat demokratis dan dapat melibatkan para karyawannya secara langsung dalam memutuskan keputusan nantinya akan di ambil oleh perusahaan (Chrishienty 2015, Qurbani & Solihin, 2021).…”
Section: Quality Of Work Life (Y)unclassified